Bariery w komunikacji publicznej (studium przypadku na przykładzie polilogu medialnego) - Pałuszyńska, Edyta (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
The purpose of the article is to investigate the causes of communication disruption at different levels of discourse. The study material consisted of conversations conducted by M. Olejnik in the TV show Prosto w oczy (Straight in the Eye). The analyzed examples are taken from the episode dealing with the sources of violence against women. The analysis showed that barriers in communication were caused by a variety of factors. Some of them such as noise, low bandwidth, code limitations, information selection, or the interlocutor’s social role can be related to the communicative situation. Others can stem from the inconsistent organization of semantic discourse at the level of the thematic organization, focus, the organization of references and rhetorical organization. In the media discourse, the rhetorical organization is the most important. The specific goals of the media cause the journalist to focus not on co-operation and agreement, but on manifesting differences and on creating dramatic conflicts through simplification and polarization of attitudes.